Effect Of Active Cylindrical Exercise On The Grip Power In Stroke Patient - M. Budi Santoso; Gini Sari Puspita (Universitas Padjadjaran, 2021)
Stroke is one of the non-communicable diseases that is increasing in prevalence. One of the effects of stroke patients is weakness on one side of the body. Therefore stroke patients need rehabilitation which is fast and precise with the range of motion exercises joints; one of them is grip strength. The recommended exercise is the Active Range of Motion Cylindrical Grip. This study aimed to determine the effect of cylindrical grip on the gripping power in stroke ischemic patients. The method used is Pre-Experiment with pre and post-test one-group design. This research uses Purposive Sampling of as many as 16 ischemic stroke patients. Active Range of Motion Cylindrical Grip exercise given as much as two times a day in 10 minutes for four days. The analysis used is a nonparametric test of Wilcoxon. Results of non-parametric test analysis Wilcoxon obtained p-Value = 0.001 (α <0.05). This value indicates a significant influence between the strength value grips. It is expected that health workers can apply Active Cylindrical Grip ROM exercise as an alternative to increasing the gripping power in ischemic stroke patients who experience weakness and can improve the quality and service of healing ischemic stroke.